2021
DOI: 10.1007/s11135-021-01218-3
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods research in service-learning: an integrative systematic review

Abstract: In view of the challenges involved in designing a study of Mixed Methods (MM), as well as the problematics inherent in studying Service-Learning (S-L) from new research perspectives, and considering the lack of systematic reviews of MM in S-L, this study proposes to analyse the use of MM research to evaluate S-L through a systematic integrative review of scientific papers published in international databases (ERIC, DIALNET, SCOPUS, and Web of Science) using the terms ‘mixed methods research’ and ‘service-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…With regard to the geographical representation of the publications and methodological concerns, our results align with recent reviews (Camilli Trujillo, Cuervo Calvo, García Gil, & Bonastre Valles, 2021; Stewart & Wubbena, 2015). Although it may be affected by the language and the “Service‐Learning” term selection criteria, the prevalence of US publications (58%, n = 27) is more likely to reflect the more extensive adoption of SL programs in North America compared to other areas of the world.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to the geographical representation of the publications and methodological concerns, our results align with recent reviews (Camilli Trujillo, Cuervo Calvo, García Gil, & Bonastre Valles, 2021; Stewart & Wubbena, 2015). Although it may be affected by the language and the “Service‐Learning” term selection criteria, the prevalence of US publications (58%, n = 27) is more likely to reflect the more extensive adoption of SL programs in North America compared to other areas of the world.…”
Section: Discussionsupporting
confidence: 89%
“…Although it may be affected by the language and the “Service‐Learning” term selection criteria, the prevalence of US publications (58%, n = 27) is more likely to reflect the more extensive adoption of SL programs in North America compared to other areas of the world. Camilli Trujillo et al (2021) suggested that qualitative methodology is prevalent in SL research and asked for more methodological strength in SL research, calling for more mixed‐method studies, where qualitative data can corroborate quantitative results and lead to additional insights not gleaned from one approach alone (Creswell, 2015; Creswell & Plano Clark, 2017). The results of our review converged with those suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed-method longitudinal approach was chosen for triangulation to assess the extent to which qualitative and quantitative findings corroborate each other [ 29 ]. The choice of this approach was also determined by the reported scarcity of mixed-method studies in SL research to stimulate additional insights and further understanding not gleaned from one approach alone [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, for mixed method-systematic reviews, Pluye and Hong (2014) suggested that the phrase "mixed studies review" should be chosen over "mixed methods review" because a review that includes a mixture of studies with diverse designs is referred to as "mixed studies review," and a review that included only studies of mixed methods refer to "mixed methods review." Camilli Trujillo et al. (2021) used the concept of "Integrative Systematic Review."…”
Section: Response To Each Commentmentioning
confidence: 99%